COVID-Care – a safe and successful digital self-assessment tool for outpatients with proven and suspected coronavirus-2019. (September 2021) - Drewett, George P; Holmes, Natasha E; Trubiano, Jason A; Vogrin, Sara; Feldman, Jeff; Rose, Morgan
Introduction: The coronavirus-2019 (COVID-19) pandemic and restrictions placed on movement to prevent its transmission have led to a surge in demand for remote medical care. We investigated whether COVID-Care, a patient-reported, telehealth, symptom monitoring system, was successful at delivering safe monitoring and care for these patients leading to decreased hospital presentations. Methods: We performed a single centre, prospective, interventional cohort study with symptomatic outpatients who presented for COVID-19 screening at Austin Health, Australia. Participants were invited to take part in the COVID-Care programme, entering common COVID-19 symptoms on a purpose-built, online survey monitored by infectious diseases physicians, and matched with clinical data including date of symptom onset, hospital admission, and screening clinic presentations. Results: 42, 158 COVID-19 swabs were performed in 31, 626 patients from March to October 2020, with 414 positive cases. 20, 768 people used the COVID-Care survey at least once. COVID-Care users were significantly younger than non-users. Of the 414 positive cases, 254 (61.3%) used COVID-Care, with 160 (38.6%) non-users. Excluding presentations on the same day or prior to the COVID-19 swab, of the positive cases there were 56 hospital presentations. 4.3% (11) of COVID-Care users and 28.1% (45) non-users were admitted to hospital or the emergency department ( p  < 0.001), with 3.9% (10) versus 22.5% (36) requiring inpatient admission ( p  < 0.001). There were no deaths in COVID-Care users versus 2 deaths in non-users. Conclusion: COVID-Care, a digitally integrated, outpatient, symptom tracking and telemedical service for patients with COVID-19, was safe and successful at reducing hospital and emergency department admissions, suggesting a strong role for telemedicine for future healthcare delivery in this logistically challenging setting.